(untitled) (Bangladesh Journal of Medical Science, 2020)
Background: Dengue Shock Syndrome (DSS) is a severe manifestation of Dengue Hemorrhagic Fever (DHF) and affects more children and young adults. The age of susceptibility to DSS is 5-15 years old, due to an imperfect immune system. DHF patients with manifestations of DSS have propensity that can affect the platelet and hematocrit values as an initial laboratory parameter. Objective: This study is intended to find out the most effective platelet and hematocrit blood parameters and to find the correlation between platelet values and hematocrit on the incidence of DHF in Wirosaban Hospital of Yogyakarta Municipality in the period f March 2015 to July 2016. The data used were secondary data from medical records of pediatric patients aged 5-15 years old. Material and Methods: The research method used was to determine the correlation between platelet values and hematocrit on the incidence of DHF and DSS in children. Data analysis used chi-square to determine the correlation between platelet values and hematocrit on the incidence of DHF and DSS in children. Results and Discussion: In this study, the number of samples that fulfilled the inclusion and exclusion criteria was 74 on platelet examination while in the hematocrit examination there were 77 that met the criteria. The results of chi-square test for platelet examination obtained p value> 0.05, which means there was no significant correlation between platelet counts and the incidence of DHF, DHF grade II, and DSS. The results of the chi-square test analysis on hematocrit examination obtained p <0.05, which means that there was a significant correlation between hematocrit values and the incidence of DHF and DSS and it obtainedd r = 0.707. Conclusions: In this study the increase in hematocrit is one of the parameters to detect DHF with propensity to DSS. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.273-277